2008
DOI: 10.1073/pnas.0712262105
|View full text |Cite
|
Sign up to set email alerts
|

Distinct nuclear and cytoplasmic functions of androgen receptor cofactor p44 and association with androgen-independent prostate cancer

Abstract: Androgen receptor (AR) mediates transcriptional activation of diverse target genes through interactions with various coactivators that may alter its function and help mediate the switch between prostate cell proliferation and differentiation. We recently identified p44/MEP50 as an AR coactivator and further showed that it is expressed primarily in the nucleus and cytoplasm of benign prostate epithelial and prostate cancer cells, respectively. We also showed that haploinsufficiency in p44 ؉/؊ mice causes prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(111 citation statements)
references
References 23 publications
(26 reference statements)
3
100
0
1
Order By: Relevance
“…The molecular mechanisms underlying AR inactivation are complex and deserve further investigation in this species. In many cases, especially in prostate cells, the exportation of AR from the nucleus to the cytoplasm and their inactivation has been related to androgen withdrawal (Tyagi et al, 2000, Gregory et al, 2001, Peng et al, 2008. Given that previous gerbil hormonal data evidenced a decline in serum androgen levels only around 14 d (Siegford et al, 2003), it is probable that other cofactors might be involved in neonatal ARinactivation.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms underlying AR inactivation are complex and deserve further investigation in this species. In many cases, especially in prostate cells, the exportation of AR from the nucleus to the cytoplasm and their inactivation has been related to androgen withdrawal (Tyagi et al, 2000, Gregory et al, 2001, Peng et al, 2008. Given that previous gerbil hormonal data evidenced a decline in serum androgen levels only around 14 d (Siegford et al, 2003), it is probable that other cofactors might be involved in neonatal ARinactivation.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this, p44, an AR coregulator, is mislocalized to the cytoplasm in prostate cancer but not matched benign sections (45). Intriguingly, nuclear p44 appears to have an antiproliferative role, but cytoplasmic p44 has an opposing, proliferative role in prostate cell line growth (45,46). Further analysis of primary tumor biopsies, sequencing of HEY genes for mutations in regions important for nuclear localization, and analysis of potential sites of post-translational modification may increase our understanding of the mechanisms and significance of HEY protein exclusion in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…CDK6 was shown to be required for proper thymocyte development and tumorigenesis (Hu et al, 2009). Most recently, NANOG in embryonic stem cells, MEP50 in prostate cancer cells and Smad in osteoblast were shown to directly regulate CDK6 transcription (Ogasawara et al, 2004a;Peng et al, 2008;Zhang et al, 2009). Additional evidence of CDK6 function in developmental processes showed that CDK6 expression was regulated by developmentally important miRNAs (Johnson et al, 2007;Lujambio et al, 2007;Silber et al, 2008).…”
Section: Introductionmentioning
confidence: 99%